Digitalisasi Pemberdayaan Ekonomi Mustahiq Berbasis Zakat Produktif - Annida Karima Sovia; Delima Sari Lubis; Aliman Syahuri Zein (Journal of Islamic Social Finance Management, 2020)
Abstract              Poverty is a social problem that requires effective and sustainable management. Many parties have made various efforts to overcome poverty. However, the poverty reduction model built tends to only use a charitable approach (generosity). So that it only creates a sense of dependence on aid, without creating a productive spirit for the poor. Therefore, in facing the times, it is necessary to digitize the correct mustahiq economic empowerment model. The type of research used is in the form of field research with qualitative methods. The study concludes that the proper digitalization of the mustahiq economic empowerment model can be carried out in a creative productive manner, namely the distribution of zakat that cannot be directly used or spent by the mustahiq. So that its possible use will have an economic impact on mustahiq with guidance and assistance through digital technology. Keywords: Digitalization, Empowerment, Mustahiq, Productive